On the Development of Virtual Reality Scenarios for Computer-Assisted Biomedical Applications. (30th August 2018) - Govea-Valladares, Eder H.; Medellin-Castillo, Hugo I.; Ballesteros, Jorge; Rodriguez-Florido, Miguel A.
Abstract : The modelling of virtual environments and scenarios is an important area of research for the development of new computer-assisted systems in the areas of engineering and medicine, particularly in the area of biomechanics and biomedical engineering. One of the main issues while designing a virtual environment is the level of realism, which depends on the computing capacity and the level of accuracy and usefulness of the generated data. Thus, the dilemma is between the aesthetic realism and the information utility. This paper proposes a methodology to develop low-cost and high-quality virtual environments and scenarios for computer-aided biomedical applications. The proposed methodology is based on the open-source software Blender and the Visualization Toolkit libraries (VTK). In order to demonstrate the usability of the proposed methodology, the design and development of a computer-assisted biomedical application is presented and analysed.